624.011.15 THEORETICAL BASIS OF THE METHODOLOGY OF SELECTING WEAR-RESISTANT MATERIALS TO ABRASIVE CORROSION - Maxmudov, Iqrorxon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents the theoretical foundations of the method of choosing abrasive-resistant inedible materials. Futurmore, the concepts of abrasive eating are covered more broadly. In agriculture, it is mention about the current state of consumption of the material of the working bodies of soil processing machines. Also, abrasive anti-eating methods have also been cited, and the carbon content of the steel material, its hardness, and relative wear resistance, based on the amounts of chromium, have been analyzed.